Are we ready yet for digital transformation? Virtual versus on-campus OSCE as assessment tools in pharmacy education. A randomized controlled head-to-head comparative assessment - Zelal Kharaba; Mohammad M. AlAhmad; Asim Ahmed Elnour; Abdallah Abou Hajal; Suhad Abumweis; Mohammad A. Ghattas (Elsevier, 2023)
Background: The global COVID-19 pandemic has influenced pharmacy education including learning, assessment, and exams. In the UAE, pharmacy instructors have adapted several innovative teaching methods to strive for quality learning outcomes. The current trial presented a head-to-head comparative assessment between on-campus versus virtual Objective Structured Clinical Examination (OSCE) with examiners' and students' perspectives. Aim: The main aim was to compare fourth-year students' and examiners' perceptions of the feasibility (time and logistics), stress, performance, and satisfaction between on-campus versus virtual OSCE. Method: A randomized controlled head-to-head comparative assessment between the On-campus and virtual OSCE was conducted to explore performance and satisfaction of pharmacy students and examiners towards the two OSCE settings. The virtual OSCE was carried out directly after the on-campus -OSCE and the setting was designed in a way that aligned with the on-campus OSCE but in a virtual way. Microsoft Teams® breakout room was used as a virtual stations. Respondus-lockdown-browse and Google Meet® were used for proctoring purposes. Results: Students who sat for the on-campus assessment were more satisfied with the instructions, the orientation session, the time management, and the overall exam setting, the ability of the exam to assess their communication and clinical skills, professionalism and attitude, and the interactivity of the exam compared to the students who sat for the virtual assessment. Examiners' perceptions for both settings were the same with the exception of interaction with students (p less than 0.05) as the on-campus OSCE was more interactive. Conclusion: Students still prefer the on-campus OSCE to the virtual OSCE format in many aspects. Nevertheless, virtual OSCE is still a feasible and satisfactory method of assessment when on-campus OSCE is not possible. There is a need of a specialized platform to conduct the virtual OSCE from A to Z rather than maximizing the use of options in the current digital platforms.